Металеві ножі доби бронзи поблизу Кам’яної Могили (Західне Приазов’я) - Котова, Н.С.; Джос, В.С.; Махортих, С.В.; Радченко, С.Б. (Археологія і давня історія України, 2021)
Статтю присвячено металевим ножам доби бронзи, знайденим неподалік від відомої петрографічної та археологічної пам’ятки «Кам’яна Могила» у Запорізької області та їхнім аналогіям у похованнях ямної, катакомбної та зрубної культур. Metal (copper and bronze) knives is one of the most striking categories of artefacts in the materials of the Black Sea cultures of the Early, Middle and Late Bronze Age. In addition to introducing new archaeological evidences to scientific community, the paper aims to analyze the place of a representative series of knives (8 items) from the vicinity of Kamyana Mohyla (Zaporizhzhya region) in the cultural and chronological coordinate system of the southern part of Eastern Europe Bronze Age. Three knives came from the Yamna culture burials. The one with an oval blade of the Zarechnoe type (kurgan 1, burial 8) is similar to those used on the vast area from the North-Western Black Sea region to the North Caucasus. Knives from Novopilipovka (kurgan 6, burial 5) and Semenovka (kurgan 2, burial 1) introduce some local features and were probably produced by the local metalworking center. Four other knives are related to the Catacomb culture. The one with a sub-triangular blade and an accented handle from Zarechnoe (kurgan 7, burial 1) belongs to the artefacts that occure rarely during the Catacomb time, but was common for the Yamnaya culture in Crimea and in the Dnieper region. Other types of artefacts do not meet the analogies in Yamnaya culture burials. Knives with a leaf-shaped short blade and maximum widening in their upper part (Zarechnoe, kurgan 17, burial 4) are usually attributed to the Catacomb culture of the Seversky Donets basin and to the east of the Don river. Knives of the Kamyana Mohyla 5 type with a leaf-shaped blade and a long handle are also usually found at the Catacomb sites of the Seversky Donets basin. Knives of the Sekiz 3 type with a long handle and a short sub-rhombic blade originated in the Catacomb culture and the final Novotitorovka group. They are localized in the eastern regions (the Don basin, the Lower Volga, and the North Caucasus). A knife from the Terpinnya site is associated with the monuments of the second period of the Berezhno- Mayevskaya Srubnaya culture and is similar to the finds coming from the archaeological sites in the steppe Dnieper region and Azov Sea region in the second half of the second millennium BC. The large number of metal knives found in the studied area during the Bronze Age, which originate both from burials and settlements was probably related to the use of Kamyana Mohyla Hill as a ritual place.